Low Power Resistive Oxygen Sensor Based on Sonochemical SrTi0.6Fe0.4O2.8 (STFO40) - Alisa Stratulat; Bogdan-Catalin Serban; Andrea de Luca; Viorel Avramescu; Cornel Cobianu; Mihai Brezeanu; Octavian Buiu; Lucian Diamandescu; Marcel Feder; Syed Zeeshan Ali; Florin Udrea (Sensors, 2015)
The current paper reports on a sonochemical synthesis method for manufacturing nanostructured (typical grain size of 50 nm) SrTi0.6Fe0.4O2.8 (Sono-STFO40) powder. This powder is characterized using X ray-diffraction (XRD), Mössbauer spectroscopy and Scanning Electron Microscopy (SEM), and results are compared with commercially available SrTi0.4Fe0.6O2.8 (STFO60) powder. In order to manufacture resistive oxygen sensors, both Sono-STFO40 and STFO60 are deposited, by dip-pen nanolithography (DPN) method, on an SOI (Silicon-on-Insulator) micro-hotplate, employing a tungsten heater embedded within a dielectric membrane. Oxygen detection tests are performed in both dry (RH = 0%) and humid (RH = 60%) nitrogen atmosphere, varying oxygen concentrations between 1% and 16% (v/v), at a constant heater temperature of 650 °C. The oxygen sensor, based on the Sono-STFO40 sensing layer, shows good sensitivity, low power consumption (80 mW), and short response time (25 s). These performance are comparable to those exhibited by state-of-the-art O2 sensors based on STFO60, thus proving Sono-STFO40 to be a material suitable for oxygen detection in harsh environments.